Intergenerational Rights? - Richard Vernon (Intergenerational Justice Review)
Past injustices demand a response if they have led to present deprivation. But skeptica arthe that there is no need to introduce a self-contained concept of 'historical justice' as our general concepts of justice provide all the necessary resources to deal with present inequalities. A rights-based approach to intergenerational issues has some advantages when compared to rival approaches: those based on intergenerational community, for example, or on obligations deriving from traditional continuity. While it is possible to ascribe rights to beings who are not presently in existence, the case for ascribing rights to future generations is much stronger than for past generations.